Multidisciplinary Optimisation of Geometric Variation and Dynamic Behaviour for Squeak & Rattle - Krishnaswamy, Aswin Dhananjai; Sathappan, Chidambaram (My University, 2020)
Squeak & Rattle (S&R) are undesired sounds that are caused when two components come in contact with each other. They give the user a feeling of the possibility of a quality issue. In modern premium cars, user comfort is of utmost importance and these undesired sounds must be eliminated. There are various reasons that cause the S&R of which geometric variation is a major contributors. The variation and deviation in the assembly lead to undesired gaps between the components making them come in contact with each other. This also influences the dynamic behaviour of the components leading to resonance. However, varying the location of the attachment points could impact the cause of S&R and requires an optimisation. A benchmark study was done with various cars in different segments from different manufacturers. Assemblies that are prone to have high Squeak & Rattle were identified and a simpler version of the assembly was modelled. The simplified models were categorized into different model configurations and the optimisation was carried out. A modified Incremental Space Filler program was written to generate Design of Experiments based on certain requirements of the work. The program was created by including all the constraints making the DOE design generation faster. A two-stage genetic algorithm-based optimisation approach was used to identify the right attachment scheme between components. The findings were documented, and the methodology was also applied for some industrial cases with models from real industrial applications like Instrument Panel assembly and Side door assembly.
Keywords: Squeak and Rattle, Multidisciplinary Optimisation, Geometric variation; Dynamic response, Resonance